Copper-catalyzed carbonylative synthesis of pyrrolidine-containing amides from γ, δ-unsaturated aromatic oxime esters. Issue 19 (10th September 2020) - Zhang, Youcan; Ai, Han-Jun; Wu, Xiao-Feng
Abstract : A new method of low-cost copper-catalyzed carbonylative cyclization for preparing pyrrolidine-containing amides from γ, δ-unsaturated aromatic oxime esters and amines has been described. Abstract : A new method of low-cost copper-catalyzed carbonylative cyclization for preparing pyrrolidine-containing amides from γ, δ-unsaturated aromatic oxime esters and amines has been described. A range of readily available amines were examined, including primary, secondary, and heterocycle amines, giving over 60 examples of targeted N-heterocycle substituted amides with broad functional group tolerance, good chemical selectivity and moderate to excellent yields.